Targeted cultivation of diatoms in mariculture wastewater by nutrient regulation and UV-C irradiation - Shen, Jiacong; Zheng, Xiafei; Liu, Minhai; Xu, Kui; He, Lin; Lin, Zhihua (Frontiers in Microbiology, 2024)
Mariculture wastewater poses environmental challenges due to pollution and eutrophication. Targeted cultivation of diatoms in wastewater can help alleviate these issues while generating beneficial algae biomass, however reliable operating methods are lacking. We proposed a novel method for treating mariculture wastewater that employed UV-C irradiation and nutrient regulation to achieve targeted diatom cultivation. This study first examined growth of four diatom species (Nitzschia closterium, Chaetoceros muelleri, Cyclotella atomus, and Conticribra weissflogii) in mariculture wastewater. C. muelleri and C. weissflogii demonstrated better adaptability compared to N. closterium and C. atomus. Additionally, the growth and nutrient utilization of C. muelleri were studied under varying concentrations of silicate, phosphate, ammonium, and trace elements in wastewater. Optimal growth was observed at 500 μmol/L silicate, 0.6 mg/L phosphate, and 4 mg/L ammonium. Ammonium proved to be a more effective nitrogen source than urea and nitrate in promoting growth at this low level. Surprisingly, trace element supplementation did not significantly impact growth. Finally, this study utilized UV-C irradiation as a pre-treatment method for wastewater prior to nutrient adjustment, significantly enhancing the growth of C. muelleri. Overall, this study provides guidance on regulating key nutrients and pre-treatment method to optimize diatom biomass production from mariculture wastewater. This approach not only addresses environmental challenges associated with mariculture but also contributes to sustainable aquaculture practices through the recovery of valuable aquatic resources.